2012
DOI: 10.1183/09031936.00177011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8 weeks of continuous positive airway pressure on abdominal adiposity in obstructive sleep apnoea

Abstract: The aim of the present study was to investigate the effect of continuous positive airway pressure (CPAP) treatment on regional adipose tissue distribution in patients with moderate or severe obstructive sleep apnoea.Patients received both therapeutic and sham CPAP in a random order for 2 months each with an intervening 1-month washout. Abdominal subcutaneous, visceral and liver fat were quantified using magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS). Liver enzymes and plasma glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
67
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 33 publications
4
67
1
3
Order By: Relevance
“…In a recent randomized controlled trial, 24 weeks of CPAP treatment alone (on average z4 h per night) did not improve insulin sensitivity as assessed by ivGTT (27). Previous randomized controlled trials have found no benefit of CPAP treatment on measures of glucose metabolism when the duration of average CPAP use ranged from 3.3 to 6.2 hours per night (20)(21)(22)(23)(24)(25)(26)(27)(28). In one controlled study involving individuals with prediabetes, 2 months of CPAP use (on average z4.8 h per night) led to an improvement in insulin sensitivity only in those who had severe OSA (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent randomized controlled trial, 24 weeks of CPAP treatment alone (on average z4 h per night) did not improve insulin sensitivity as assessed by ivGTT (27). Previous randomized controlled trials have found no benefit of CPAP treatment on measures of glucose metabolism when the duration of average CPAP use ranged from 3.3 to 6.2 hours per night (20)(21)(22)(23)(24)(25)(26)(27)(28). In one controlled study involving individuals with prediabetes, 2 months of CPAP use (on average z4.8 h per night) led to an improvement in insulin sensitivity only in those who had severe OSA (29).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this strong association between OSA and alterations in glucose metabolism, there is still controversy as to whether treatment of OSA with continuous positive airway pressure (CPAP) has metabolic benefits (18,19). Prior randomized controlled trials investigating the effects of CPAP on measures of glucose metabolism yielded mostly negative results (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The average duration of CPAP use in these trials ranged from 3.3 to 6.2 hours per night.…”
mentioning
confidence: 99%
“…6 Most, but not all studies report that visceral fat does not decrease with CPAP use. 4,5,[7][8][9] Moreover, in the study by Muntzer et al, 4 there was a trend for an increase in visceral fat with CPAP, although it did not reach statistical signifi cance. However, waist circumference 4 and subcutaneous fat 5 increased.…”
mentioning
confidence: 93%
“…Our findings are in agreement with the only randomized placebo controlled study by Kohler et al [38] who did not find any effect of therapeutic CPAP treatment for 4 weeks on liver enzymes compared to sham CPAP. Sivam et al [39] in a randomized double-blinded sham controlled trial of CPAP for 8 weeks reported no effect of CPAP on liver enzyme. In contrast to [40] demonstrated abnormal serum aminotransferase levels in 35% of obese OSAS patients included in the study.…”
Section: Discussionmentioning
confidence: 99%